DOMINATION, DECEPTION, AND DESTRUCTION: TOXIC MASCULINITY IN DELIA OWENS' WHERE THE CRAWDADS SING - Agung, I Gusti Ayu Mahatma (CALL, 2025)
The study examines how toxic masculine behaviors are represented in the novel Where the Crawdads Sing by Delia Owens. Using Makhanya's (2023) theory on the hazardous effects of masculinity as a framework, the study focuses on the various forms of toxic masculinity and their impacts on the characters. The findings reveal four types of toxic masculine behaviors in the novel: overcompensation through risky behavior, ineffective conflict resolution strategies, domestic abuse and power dynamics, and sexual assault. Among these, domestic abuse and power dynamics emerge as the most dominant form. The analysis highlights how male characters embody these harmful traits to assert dominance and control, perpetuating cycles of violence and trauma. In conclusion, toxic masculinity operates as a deeply rooted cultural problem, reinforcing patriarchal structures and leaving lasting emotional scars on its victims. This portrayal demonstrates that toxic masculinity is not merely an individual flaw but a systemic issue that perpetuates control, violence, and the silencing of women in both private and public spheres.